Unique equilibrium in rent-seeking contests with a continuum of types - Christian Ewerhart (University of Zurich, Department of Economics, 2014)
It is shown that rent-seeking contests with continuous and independent type distributions possess a unique pure-strategy Nash equilibrium.
Keywords: C7; D7; D8; 330; Rent-seeking; Private information; Pure-strategy Nash equilibrium; Existence; Uniqueness